Age differential response to bevacizumab therapy in choroidal neovascularization in rabbits. (October 2022) - Nguyen, Van Phuc; Henry, Jessica; Zhe, Josh; Kieu, Quynh; Qian, Wei; Fu, Yingbin; Wang, Xueding; Paulus, Yannis M.
Abstract: Choroidal neovascularization (CNV) in young rabbits has been shown to have a rapid, robust response after treatment with bevacizumab, an anti-vascular endothelial growth factor (VEGF) medication. This investigation evaluates an age differential response to bevacizumab in older populations of rabbits using multimodal high resolution molecular imaging. Young (4 months old) and life span (14 months old) rabbits were given subretinal injections of Matrigel and VEGF to produce CNV. All CNV rabbit models were then treated with a bevacizumab intravitreal injection. Rabbits were then monitored longitudinally using photoacoustic microscopy (PAM), optical coherence tomography (OCT), color photography, and fluorescence imaging. Chain-like gold nanoparticle clusters (CGNP) conjugated with tripeptide arginylglycylaspartic acid (RGD) was injected intravenously for molecular imaging. Robust CNV developed in both young and old rabbits. After intravitreal bevacizumab injection, fluorescence signals were markedly decreased 90.13% in the young group. In contrast, old rabbit CNV area decreased by only 10.56% post-bevacizumab treatment. OCT images confirmed a rapid decrease of CNV in the young group. CGNPs demonstrated high PAM signal in old rabbits and minimal PAM signal in young rabbits after bevacizumab, indicating CNV regression. There is a significant difference in response to intravitreal bevacizumab treatment between young and old rabbits with CNV which can be monitored with multimodal molecular imaging. Old rabbits demonstrate significant persistent disease activity. This represents the first large eye model of persistent disease activity of CNV and could serve as the foundation for future investigations into the mechanism of persistent disease activity and the development of novel therapies. Highlights: Comparison of CNV treatment in young and aged large animal models to demonstrate persistent disease activity in different ages of individuals. There is a significant difference in response to intravitreal bevacizumab treatment between young and old rabbits with CNV. Robust CNV developed in both young and old rabbits by subretinal injection of VEGF and Matrigel with a100% success rate. CNV was reduced by more than 90% in young rabbits while life-span rabbits demonstrate significant persistent disease activity with only 10.56% reduction in CNV. Contrast agents demonstrated high PAM signal in old rabbits and minimal PAM signal in young rabbits after bevacizumab, indicating CNV regression.